El campamento participativo : por qué la representación política no es virtuosa en sí misma, sino en todo caso un mal necesario - Maisley, Nahuel (2016)
In this paper I defend the idea that political representation is a necessary evil, that direct participation is indispensable to democratize decision-making procedures and that, thus, the content of the right to take part in the conduct of public affairs must be read under this light. For this purpose, first, I present an affirmative argument regarding the ideal of self-government as an ideal of full participation. Then, I try to answer the arguments presented by what I describe as two lines of "representativist" thought: a classic, madisonian, line of thought, reluctant to any idea of participation, and another, more modern, which admits some space for participation. Later, I consider the impact of these discussions on the interpretation of the human right to take part in the conduct of public affairs. Finally, I sum up the argument